Airway Hyperresponsiveness: New Insights into the Pathogenesis - Lommatzsch, Marek (Seminars in Respiratory and Critical Care Medicine, 2012)
Airway hyperresponsiveness (AHR) is the most characteristic clinical feature of asthma. The pathogenesis of AHR in asthma is characterized by a variety of epithelial, microbial, and inflammatory triggers on one hand and abnormalities of effector structures in the airways such as smooth muscle cells, blood vessels, and nerves on the other hand. Obesity is increasingly recognized as an important additional factor in the diagnosis and the pathogenesis of AHR in asthma. It is important to note that structural changes in the asthmatic airway can persist in the absence of inflammation. This may be one reason for the observation that potent new antiinflammatory drugs for the treatment of asthma have only little impact on AHR. New therapeutic strategies are, therefore, needed to modulate structural and functional changes in the airways, especially in patients with treatment-resistant severe asthma.
Keywords: asthma; airway hyperresponsiveness; inflammation; smooth muscle; nerves